Heterostructures Built through Site‐Selective Deposition on Anisotropic Plasmonic Metal Nanocrystals and Their Applications. Issue 12 (13th October 2021) - Yang, Xueqing Q.; Lu, Yao; Liu, Yi; Wang, Jing; Shao, Lei; Wang, Jianfang F.
Abstract : Plasmonic heterostructures composed of plasmonic metal nanocrystals (NCs) and semiconductors or metals have been attracting extensive attention due to their extraordinary properties and potential applications. Site‐selective deposition of semiconductors or metals on anisotropic plasmonic metal NCs delivers more advantages than the core@shell nanostructure counterparts. The obtained heterostructures are generally called anisotropic plasmonic heterostructures. They have been used in many research fields, including optoelectronics, biotechnologies, catalysis, and light harvesting. Herein, recent advancements on anisotropic plasmonic heterostructures are comprehensively summarized. The unique plasmonic properties of anisotropic metal NCs and various types of deposited materials are reviewed. The preparation strategies and applications of anisotropic plasmonic heterostructures with partially deposited functional materials are then thoroughly described. Site‐selective overgrowth of a semiconductor or metal component on plasmonic metal NCs can be achieved through galvanic replacement, capping agent‐directed synthesis, surface‐protected growth, and so on. According to their excellent properties, anisotropic plasmonic heterostructures enable applications in surface‐enhanced Raman spectroscopies, plasmon‐enhanced fluorescence, photocatalysis, electrocatalysis, as well as photothermal conversion and therapy. A detailed overview of future research perspectives toward the exploration of new properties and new applications of anisotropic plasmonic heterostructures, turning these distinctive nanomaterials into practically useful technologies, is provided. Abstract : Anisotropic heterostructures made of plasmonic nanocrystals deposited with functional nanomaterials in a site‐selective manner are promising for applications ranging from enhanced melocular sensing to photocatalysis. Herein, the recent development of such plasmonic structures, with the emphasis on their preparation strategies and applications, is focused on. The challenges and future research perspectives are also discussed.